Molecular and morphological identification of suspected Plasmodium vivax vectors in Central and Eastern Sudan - Omnia Fathelrhman Abdelwhab; Arwa Elaagip; Musab M. Albsheer; Ayman Ahmed; Giacomo Maria Paganotti; Muzamil Mahdi Abdel Hamid (Malaria Journal, 2021)
Abstract Background In spite of the global effort to eliminate malaria, it remains the most significant vector-borne disease of humans. Plasmodium falciparum is the dominant malaria parasite in sub-Saharan Africa. However, Plasmodium vivax is becoming widely spread throughout Africa. The overuse of vector control methods has resulted in a remarkable change in the behaviour of mosquito that feeds on human as well as on vector composition. The aim of this study was to identify Anopheles mosquito species in vivax malaria endemic regions and to investigate their role in P. vivax circumsporozoite protein (Pvcsp) allele diversity. Methods Mosquito samples were collected from Central Sudan (Rural Khartoum and Sennar) and Eastern Sudan (New Halfa, Kassala state) using pyrethrum spray catch (PSC) and CDC light traps. Mosquitoes were identified using appropriate morphological identification keys and Anopheles gambiae complex were confirmed to species level using molecular analysis. A subset of blood-fed anopheline mosquitoes were dissected to determine the presence of natural infection of malaria parasites. In addition, the rest of the samples were investigated for the presence of Pvcsp gene using nested-PCR. Results A total of 1037 adult anopheline mosquitoes were collected from New Halfa (N = 467), Rural Khartoum (N = 132), and Sennar (N = 438). Morphological and molecular identification of the collected mosquitoes revealed the presence of Anopheles arabiensis (94.2%), Anopheles funestus (0.5%), and Anopheles pharoensis (5.4%). None of the dissected mosquitoes (N = 108) showed to be infected with malaria parasite. Overall P. vivax infectivity rate was 6.1% (63/1037) by Pvcsp nested PCR. Co-dominance of An. arabiensis and An. pharoensis is reported in Sennar state both being infected with P. vivax. Conclusion This study reported P. vivax infection among wild-caught anopheline mosquitoes in Central and Eastern Sudan. While An. arabiensis is the most abundant vector observed in all study areas, An. funestus was recorded ...